Turbulent energy budget analysis based on coherent wind lidar observations - J. Xian; J. Xian; Z. Qiu; H. Luo; Y. Hu; X. Lin; C. Lu; Y. Yang; H. Yang; N. Zhang; N. Zhang (Atmospheric Chemistry and Physics)
The turbulent kinetic energy (TKE) budget terms, which collectively are a key physical quantity for describing the generation and dissipation processes of turbulence, are crucial for revealing the essence and characteristics of turbulence. Due to limitations in current observational methods, the generation and dissipation mechanisms of atmospheric turbulent energy are mainly based on ground or tower-based observations, and studies on the budget terms of TKE of vertical structures are lacking. We propose a new method for detecting TKE budget terms based on coherent wind lidar and compare it with data obtained with a three-dimensional ultrasonic anemometer. The results indicate that the error in the buoyancy generation term estimated by the wind lidar is relatively small, less than 0.00014 m2 s−3, which verifies the accuracy and reliability of our method. We explore the generation and dissipation mechanisms of turbulence under different weather conditions, and find that the buoyancy generation term plays a role in dissipating TKE under low-cloud and light-rain conditions. During the day, turbulent transport and the dissipation rate are the main dissipation terms, while buoyancy generation is the main dissipation term at night. The results show that the proposed method can accurately capture the vertical distribution of TKE, the dissipation rate, shear generation, turbulent transport, and buoyancy generation terms in the boundary layer and can comprehensively reflect the influence of each budget term on the vertical structure of turbulent energy. This research provides a new perspective and method for studies of atmospheric turbulence, which can be further applied to fine observations of the vertical structure and dynamics of turbulence.